OUTCOME OF THE INVERTED INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE FOR THE REPAIR OF LARGE IDIOPATHIC MACULAR HOLES - Jamil, Muhammad Usman; Rizvi, Syed Fawad; Mahmood, Aysal (Journal of Ayub Medical College Abbottabad, 2023)
Background: Full-thickness macular hole is defined as an anatomical defect in the fovea that spans from the internal limiting membrane to the retinal pigment epithelium, assessed by spectral-domain optical coherence tomography. The Objectives of the study are to determine the anatomical and visual outcome in patients undergoing pars plana vitrectomy along with inverted internal limiting flap closure in large idiopathic full-thickness macular holes (>400 Î¼m). Methods: A prospective interventional study was conducted at a tertiary teaching eye hospital in Karachi, where patients of either gender and having macular holes greater than >400 Î¼m were recruited. The study was conducted From January 9 to July 8, 2022, and all patients underwent pre-operative fundus examination and pars plana vitrectomy with inverted ILM flap closure. Data was entered and analyzed using SPSS 23. Follow-ups were conducted at 1 and 3 months. Results: A total of 94 patients were enrolled with a mean age of 49.17±13.8 years. The mean duration of symptoms was 3.1±1.4 months. The mean pre-operative macular hole diameter was 854.31±08.36 Î¼m and Stage 3 and 4 MH was present in 36.2% and 63.8% of patients, respectively. Anatomical closure was achieved in 93.6% of eyes (n=88/94). Pre-operative mean BCVA was LogMAR 0.90±0.24, which improved to LogMAR mean 0.70±0.27 at the final follow-up. As of the last follow-up, 92.6% of patients showed improved visual outcomes, with a mean three-line improvement in Snellen lines. After data stratification, no statistically significant result was obtained. Conclusion: The use of the inverted ILM flap technique resulted in improved anatomical and visual outcomes, in cases of large idiopathic macular holes